Pengembangan Sistem Otomatisasi Use Case Diagram berdasarkan Skenario Sistem menggunakan Metode POS Tagger Stanford NLP - Muhammad Aji Taufan; Denny Sagita Rusdianto; Mahardeka Tri Ananta (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2022)
Use case diagrams are a fundamental thing in software modeling. This is because of its function states the interaction that occurs between user and system visually and presents all functions that will be carried out by the system briefly, concisely and clearly. However, to get a good use case diagram, good results of writing requirements and qualified elicitation analysis are needed so that it takes up too much time. One way to facilitate this is by automating the creation of use case diagrams. The system automation in this study is a modeling recommendation. Use case diagrams can be generated with system scenarios as input because they represent existing elements. Then to translate the scenario into use case diagrams are using natural language processing stanfordNLP and the plantUML library for making automation diagrams. The research was conducted by analyzing requirements and obtaining 7 functional requirements. The system development model that will be developed uses the waterfall with Java as its programming language because it could be integrated with the stanfordNLP and plantUML libraries. The system will be developed on a desktop and can be run on a platform that supports JRE (Java Runtime Environment). The next stage is unit, integration and validation and accuracy testing, with the results of the unit test procedure being 100% valid from 3 samples, validation testing 100% valid from all test cases and results of accuracy testing on usage scenarios between 47% to 64%.